C81‐evoked inhibition of the TNFR1‐NFκB pathway during inflammatory processes for stabilization of the impaired vascular endothelial barrier for leukocytes. Issue 6 (27th May 2021) - Krishnathas, G. Melissa; Strödke, Benjamin; Mittmann, Laura; Zech, Thomas; Berger, Lena M.; Reichel, Christoph A.; Rösser, Silvia; Schmid, Tobias; Knapp, Stefan; Müller, Susanne; Bracher, Franz; Fürst, Robert; et al.
Abstract: Chronic inflammation‐related diseases are characterized by persistent leukocyte infiltration into the underlying tissue. The vascular endothelium plays a major role in this pathophysiological condition. Only few therapeutic strategies focus on the vascular endothelium as a major target for an anti‐inflammatory approach. In this study, we present the natural compound‐derived carbazole derivative C81 as chemical modulator interfering with leukocyte‐endothelial cell interactions. An in vivo assay employing intravital microscopy to monitor leukocyte trafficking after C81 treatment in postcapillary venules of a murine cremaster muscle was performed. Moreover, in vitro assays using HUVECs and monocytes were implemented. The impact of C81 on cell adhesion molecules and the NFκB signaling cascade was analyzed in vitro in endothelial cells. Effects of C81 on protein translation were determined by incorporation of a puromycin analog‐based approach and polysome profiling. We found that C81 significantly reduced TNF‐activated leukocyte trafficking in postcapillary venules. Similar results were obtained in vitro when C81 reduced leukocyte‐endothelial cell interactions by down‐regulating cell adhesion molecules. Focusing on the NFκB signaling cascade, we found that C81 reduced the activation on multiple levels of the cascade through promoted IκBα recovery by attenuation of IκBα ubiquitination and through reduced protein levels of TNFR1 caused by protein translation inhibition. We suggest that C81 might represent a promising lead compound for interfering with inflammation‐related processes in endothelial cells by down‐regulation of IκBα ubiquitination on the one hand and inhibition of translation on the other hand without exerting cytotoxic effects.